PELATIHAN PEMBUATAN PROPOSAL DAN LAPORAN PENELITIAN TINDAKAN KELAS BAGI GURU-GURU SMP KOTA PAGARALAM - Alwi, Zahra; SUPRIYADI, SUPRIYADI; MUKMIN, SUHARDI; Ansori, Ansori (Universitas Sriwijaya, 2019)
The community service activities undertaken are aimed at helping teachers to be able to design, implement, and report classroom action research (CAR) so that they can improve the ability of teachers to write and facilitate their promotion, as well as to improve the quality of the process and learning outcomes. The method of implementing this service is training with a variety of methods, including: lectures, questions and answers, discussions, models, and group assignments, which are carried out integrally. The material presented includes the concept of CAR, procedures, benefits, systematic proposal accompanied by examples, systematic reports, and sample papers of CAR results. The target audience is 23 teachers who are members of the MGMP, the activity is carried out at SMAN 1 Kota Pagar Alam, 19-21 October 2019. The design of the evaluation uses pretest and posttest. The results of the posttest (71.40) are greater than the pretest (47.82), showing that the ability of the participants has improved after receiving training, the participants are very active and enthusiastic, they also succeeded in making a CAR proposal which will be followed up in their respective schools, resulting in reports that can be made papers or articles (on going). Participants and the Ministry of Education hope that similar activities can continue and in the future there needs to be cooperation with the FKIP Unsri.